The Secret garden - Burnett, Frances Hodgson (London : Puffin, 1993)
A ten years-old orphan comes to live in a lonely house on the Yorkshire moors and discovers on invalid cousin and the mysteries of a locked garden.
Keywords: Gardens -- Fiction; Physically handicapped -- Fiction